2007
DOI: 10.1097/01.brs.0000251069.58498.eb
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Skills and Balance Strategies in Adolescents Idiopathic Scoliosis

Abstract: Patients with AIS show substantial similarities with control subjects in adaptive strategies relative to locomotor velocity as well as balance control based on segmental stabilization. In contrast, the loss of the yaw head stabilization strategies, mainly based on the use of vestibular information, probably reflects the presence of vestibular deficits in the patients with AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 24 publications
2
29
1
4
Order By: Relevance
“…This concurs with the observation that the phenotype of body distortion and skeletal deformations in human AIS are also rather variable (Weinstein et al, 2008). Assuming a general validity of the results in Xenopus, the gaze/ posture deficits that accompany human AIS (Jensen and Wilson, 1979;Byl et al, 1997;Wiener-Vacher and Mazda, 1998;Rousie et al, 1999;Manzoni and Miele, 2002;Mirovsky et al, 2006;Mallau et al, 2007) are compatible with a common vestibular origin, although a secondary influence of the distorted skeletal geome- -66). A, B, 3D reconstructed micro-CT scans of the vertebral column in a young adult control frog (A) and a frog that receivedaULatpre-metamorphicstage56(B).C, Opticalextractionof3vertebrae(v2,v5,v8)and3DgridofthedeformationinayoungadultULfrog.D,Planeandaxisofrotationofv2,v5,andv8inthecoronal plane;␣indicatestherotationoftheactualfrontalplane(red)ofthevertebrarelativetothetheoreticalcoronalplane(green);␤indicatestherotationofthevertebralaxis(green)relativetothedorsoventralaxis (blue).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This concurs with the observation that the phenotype of body distortion and skeletal deformations in human AIS are also rather variable (Weinstein et al, 2008). Assuming a general validity of the results in Xenopus, the gaze/ posture deficits that accompany human AIS (Jensen and Wilson, 1979;Byl et al, 1997;Wiener-Vacher and Mazda, 1998;Rousie et al, 1999;Manzoni and Miele, 2002;Mirovsky et al, 2006;Mallau et al, 2007) are compatible with a common vestibular origin, although a secondary influence of the distorted skeletal geome- -66). A, B, 3D reconstructed micro-CT scans of the vertebral column in a young adult control frog (A) and a frog that receivedaULatpre-metamorphicstage56(B).C, Opticalextractionof3vertebrae(v2,v5,v8)and3DgridofthedeformationinayoungadultULfrog.D,Planeandaxisofrotationofv2,v5,andv8inthecoronal plane;␣indicatestherotationoftheactualfrontalplane(red)ofthevertebrarelativetothetheoreticalcoronalplane(green);␤indicatestherotationofthevertebralaxis(green)relativetothedorsoventralaxis (blue).…”
Section: Discussionsupporting
confidence: 77%
“…An impaired postural and locomotor performance Mallau et al, 2007), as well as deficits in extraocular motor control and gaze stabilization (Wiener-Vacher and Mazda, 1998;Rousie et al, 1999), including spontaneous and positional nystagmus (Jensen and Wilson, 1979;, was encountered in many patients. Most of these symptoms are compatible with a bilateral imbalance of the activity in central vestibular neurons (WienerVacher and Mazda, 1998;Manzoni and Miele, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Such differences include decreased step length [6][7][8] and reduced range of motion (ROM) in the upper and lower extremities (LE) [6], but one study showed no difference [9]. It has also been reported that the gait pattern is symmetrical in healthy populations [10][11][12][13], but marked differences have been found between affected and unaffected limbs in pathological gait [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the parameters analysed was greater for scoliotic patients than for control subjects [4], especially in the mediolateral (ML) and anteroposterior (AP) directions [16,30]. The dynamical strategies observed have been found to result in slower movements during normal walking, walking on a beam, and lateral stepping [4,22].…”
Section: Introductionmentioning
confidence: 96%